Advancing the Mechanical Performance of Glasses: Perspectives and Challenges - Wondraczek, Lothar; Bouchbinder, Eran; Ehrlicher, Allen; Mauro, John C.; Sajzew, Roman; Smedskjaer, Morten M. (Advanced Materials, 2022)
Glasses are materials that lack a crystalline microstructure and long-range atomic order. Instead, they feature heterogeneity and disorder on superstructural scales, which have profound consequences for their elastic response, material strength, fracture toughness, and the characteristics of dynamic fracture. These structure–property relations present a rich field of study in fundamental glass physics and are also becoming increasingly important in the design of modern materials with improved mechanical performance. A first step in this direction involves glass-like materials that retain optical transparency and the haptics of classical glass products, while overcoming the limitations of brittleness. Among these, novel types of oxide glasses, hybrid glasses, phase-separated glasses, and bioinspired glass–polymer composites hold significant promise. Such materials are designed from the bottom-up, building on structure–property relations, modeling of stresses and strains at relevant length scales, and machine learning predictions. Their fabrication requires a more scientifically driven approach to materials design and processing, building on the physics of structural disorder and its consequences for structural rearrangements, defect initiation, and dynamic fracture in response to mechanical load. In this article, a perspective is provided on this highly interdisciplinary field of research in terms of its most recent challenges and opportunities.
CRIS-Team Scopus Importer:2023-04-20
Keywords: bioinspired composites; glass; hybrid glasses; mechanical properties; oxide glass